(untitled) (Jurnal Bahasa, 2018)
The Kelantan Malay dialect often leads towards one resolution, which is the Kelantan Malay dialect in Kota Bharu and its surrounding areas that are generally known as the downstream area. As a result, there is no information about the dialect spoken in the upstream area especially in the Gua Musang territory. This paper aims to evaluate this particular issue by making the Malay dialect spoken in Sungai Nenggiri, Hulu Kelantan, as the object of study. Preliminary analysis of phonetic and phonological features and other linguistic aspects of five villages located along the Nenggiri River found that the Malay dialect in the area showed significant differences from the Malay dialect spoken in the downstream area. These findings have two important implications, namely (1) separation exists between the Malay dialect in the upstream area with the Malay dialect downstream along the Kelantan River basin. As such, (2) Malay dialect in Kelantan and in the East Coast of the Peninsular require a new grouping. Keywords: Malay dialect, eastern Malay dialect, Hulu Kelantan Malay, Kelantan Malay, upstream and downstream